Children’s giving: moral reasoning and moral emotions in the development of donation behaviors - Ongley, Sophia F.; Nola, Marta; Malti, Tina (Frontiers in Psychology, 2014)
This study investigated the role of moral reasoning and moral emotions (i.e., sympathy and guilt) in the development of young children’s donating behavior (N = 160 4- and 8-year-old children). Donating was measured through children’s allocation of resources (i.e., stickers) to needy peers and was framed as a donation to “World Vision”. Children’s sympathy was measured with both self- and primary caregiver-reports and participants reported their anticipation of guilt feelings following actions that violated prosocial moral norms, specifically the failure to help or share. Participants also provided justifications for their anticipated emotions, which were coded as representing moral or non-moral reasoning processes. Children’s moral reasoning emerged as a significant predictor of donating behavior. In addition, results demonstrated significant developmental and gender effects, with 8-year-olds donating significantly more than 4-year-olds and 4-year-old girls making higher value donations than boys of the same age. We discuss donation behaviors within the broader context of giving and highlight the moral developmental antecedents of giving behaviors in childhood.